1998
DOI: 10.1126/science.280.5362.441
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Rising Atmospheric Carbon Dioxide on Model Terrestrial Ecosystems

Abstract: In model terrestrial ecosystems maintained for three plant generations at elevated concentrations of atmospheric carbon dioxide, increases in photosynthetically fixed carbon were allocated below ground, raising concentrations of dissolved organic carbon in soil. These effects were then transmitted up the decomposer food chain. Soil microbial biomass was unaffected, but the composition of soil fungal species changed, with increases in rates of cellulose decomposition. There were also changes in the abundance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(141 citation statements)
references
References 25 publications
5
133
3
Order By: Relevance
“…Indeed, Jones et al (1998) observed increases in fungal abundance in response to elevated CO 2 . In their study, changes observed in soil fungi at elevated CO 2 were thought to be related to increased concentrations of dissolved organic C in the rhizosphere and to increases in soil-water dissolved organic N. In one of our studies (Drigo et al 2007), we also demonstrated that elevated CO 2 increased the fungal biomass, but not the size of the bacterial community.…”
Section: Effects Of Elevated Co 2 On the Microbial Communities In Thementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Jones et al (1998) observed increases in fungal abundance in response to elevated CO 2 . In their study, changes observed in soil fungi at elevated CO 2 were thought to be related to increased concentrations of dissolved organic C in the rhizosphere and to increases in soil-water dissolved organic N. In one of our studies (Drigo et al 2007), we also demonstrated that elevated CO 2 increased the fungal biomass, but not the size of the bacterial community.…”
Section: Effects Of Elevated Co 2 On the Microbial Communities In Thementioning
confidence: 99%
“…Nevertheless, microbial biomass measurements based on cell component ATP, phospholipid fatty acid analyses (PLFA), chloroform fumigation assays, or total cell counts have yielded mixed results. Quantitative alterations in C supply have been shown to decrease (Diaz et al 1993;Ebersberger et al 2004), increase (Hungate et al 2000;van Ginkel and Gorrisen 1998;van Ginkel et al 2000;Williams et al 2000;Zak et al 1993), or not affect (Chung et al 2006;Hungate et al 2000;Kandeler et al 1998;Lussenhop et al 1998;Randlett et al 1996;Richter et al 2003) microbial biomass and activities (e.g., decomposition and nutrient cycling (Hu et al 1999;Jones et al 1998). Indeed, after 3 months of fumigation with 700 ppm 14 CO 2 , a 42% increase in microbial biomass was measured in Lolium perenne soil (van Ginkel and Gorrisen 1998;van Ginkel et al 2000).…”
Section: Effects Of Elevated Co 2 On the Microbial Communities In Thementioning
confidence: 99%
“…These observations indicate that trophic interactions figure prominently in whether microbial biomass declines or does not change under elevated CO # and whether greater turnover of microbial cells increases the flow of C and N in the plant-soil system. Such a response has the potential to influence the composition and function of soil food webs by altering bacterial and fungal assemblages (Schortenmeyer et al, 1996 ;Jones et al, 1998) and modifying their use of plantderived substrates (Rillig et al, 1997 ;Hungate et al, 2000). Clearly, there is much to be learned about the composition and function of soil food webs and how they might be altered by changes in substrate availability under elevated CO # .…”
Section: Soil Microbial Biomassmentioning
confidence: 99%
“…Plant production fuels the flow of energy through soil food webs, and several studies have documented that greater below-ground plant growth under elevated CO # can stimulate the transfer of C from organisms occupying low trophic levels (i.e. bacteria and fungi) to those higher in the soil food web such as protozoa, nematodes and collembola Yeates et al, 1997 ;Jones et al, 1998 ;Lussenhop et al, 1998 ;Hungate et al, 2000). In some studies, bacterial or fungal biomass declined by a small margin under elevated CO # , the result of enhanced predation by larger populations of protozoa, nematodes or collembola.…”
Section: Soil Microbial Biomassmentioning
confidence: 99%
“…A plant's response to elevated CO 2 seems to be not only species-specific (e.g. Bazzaz et al 1992;Farnsworth and Bazzaz 1995;Jones et al 1998) and dependent on the plant's growth stage and nutrient availability (this study ;Ko¨rner 1995;Thomas and Jasienski 1996), but can also differ between succeeding plant generations. Biomass responses showed a similar intergenerational trend to elevated CO 2 , with second-generation plants being more responsive than first-generation plants.…”
Section: Multigeneration Responsesmentioning
confidence: 99%